Eficiencia relativa da tecnologia da informação no desempenho organizacional dos Institutos Federais de Educação - Queiroz, Stenio Wagner Pereira de (2018)
The study of the impacts of the investments in Information Technology (IT) on the results of the organizations gained relevance from the emergence of the productivity paradox. Since then, this subject has been widely explored by researchers and IT specialists, but the results of the research until today do not lead to a consensus that allows categorically affirming the denial or acceptance of this paradox. On the other hand, there is agreement that the impact of IT on the organization's results depends on how it is used. In this context, IT Governance, by providing the alignment between IT strategies and business strategy, stands out as an instrument capable of providing greater efficiency of IT investments. Thus, the present work has proposed to carry out a research on the information technology in the Federal Institutes of Education with the use of the Data Envelopment Analysis (DEA) method for the years 2012 and 2014. For this it was defined as input factors the IT investments and the level of IT governance and for the factors of outputs the organizational performance in the administrative and academic scope of 31 Federal Institutes. As a result, it was possible to verify that 56.67% and 60% of the Federal Institutes analyzed were able to reach the maximum efficiency level in 2012 and 2014 respectively. It was also verified that the main cause of inefficiency in 2012 was the expenditure on investments and current expenditures per student, represented by the ADM_2 factor, while in 2014, the inefficiency was due to the expenses with personnel and expenses with other costs, portrayed by the factor ADM_1, in addition to the relation student egress by enrollment and retention of the school flow, components of the ACAD_2 factor.